An upstream open reading frame regulates vasculogenic mimicry of glioma via ZNRD1‐AS1/miR‐499a‐5p/ELF1/EMI1 pathway. Issue 11 (5th May 2020) - Wang, Mo; Yang, Chunqing; Liu, Xiaobai; Zheng, Jian; Xue, Yixue; Ruan, Xuelei; Shen, Shuyuan; Wang, Di; Li, Zhen; Cai, Heng; Liu, Yunhui
Abstract: Increasing evidence has suggested that gliomas can supply blood through vasculogenic mimicry. In this study, the expression and function of ZNRD1‐AS1‐144aa‐uORF (144aa‐uORF) and some non‐coding RNAs in gliomas were assessed. Real‐time quantitative PCR or Western blot was used to discover the expression of 144aa‐uORF, ZNRD1‐AS1, miR‐499a‐5p, ELF1 and EMI1 in gliomas. In addition, RIP and RNA pull‐down assays were applied to explore the interrelationship between 144aa‐uORF and ZNRD1‐AS1. The role of the 144aa‐uORF1‐AS1‐499a‐5p11 axis in vasculogenic mimicry formation of gliomas was analysed. This study illustrates the reduced expression of the 144aa‐uORF in glioma tissues and cells. Up‐regulation of 144aa‐uORF inhibits proliferation, migration, invasion and vasculogenic mimicry formation within glioma cells. The up‐regulated 144aa‐uORF can increase the degradation of ZNRD1‐AS1 through the nonsense‐mediated RNA decay (NMD) pathway. Knockdown of ZNRD1‐AS1 inhibits vasculogenic mimicry in glioma cells by modulating miR‐499a‐5p. At the same time, miR‐499a‐5p is down‐regulated and has a tumour‐suppressive effect in gliomas. In addition, ZNRD1‐AS1 serves as a competitive endogenous RNA (ceRNA) and regulates the expression of ELF1 by binding to miR‐499a‐5p. Notably, ELF1 binds to the promoter region of EMI1 and up‐regulates EMI1 expression, while simultaneously promoting vasculogenic mimicry in glioma cells. This study suggests that the 144aa‐uORF1‐AS1‐499a‐5p11 axis takes key part in regulating the formation of vasculogenic mimicry in gliomas and may provide a potential target for glioma treatment.